Journey to the sublime porte : the Arabic memoir of a Sharifian Agent’s diplomatic mission to the Ottoman Imperial Court in the era of Suleyman the magnificent the relevant text from Qutb al-Din al-Nahrawali’s al-Fawa’id al-saniyah fi al-rihlah al-madaniyah wa al-Rumiyah - Nahrawali, Muhammad ibn Ahmad. (Beirut ; Würzburg)
xxiii, 367 s.